Exploring the evolution of physical education and school health research: A bibliometric analysis - Perdima, Feby Elra; Abdullah, Khairul Hafezad; Karimi, Amir (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
Physical education and school health have received more attention in recent years due to the growing concern over sedentary lifestyles and the rising prevalence of obesity and other health problems among children and adolescents. As a result, there has been an increase in the study on this topic, making it crucial to assess publishing trends and identify critical areas of concentration. This study aimed to map the school physical education and health literature between 2013 and 2022. VOSviewer was used to analyse 1,427 article documents. This study indicated that 2019 was the peak year for publications, with 183 documents. This result signifies increased interest and investment in this field’s study. This publication’s rise implies that researchers, institutions, and funding agencies prioritise physical education and school health research to encourage healthy lifestyles and prevent chronic diseases in children and adolescents. The subject area “Medicine” was the most focused on physical education and school health studies, with 1,229 documents. The BMC Public Health journal published the most articles, with 165 documents. Lubans, D.R., from the University of Newcastle, Australia, was the most prolific author with 32 documents. The keyword “physical activity” was the most used in cluster 1, with 450 occurrences and a total link strength of 678. This study’s results guide the most recent references in physical education and school health to guide future research appropriately. Future research may investigate using technology and digital media to encourage physical activity and healthy lives. In addition, future research may identify methods for incorporating school health and physical education programmes.